Leonilson expandido - Silva, Lúcio Flávio Gondim da (2022)
The compass rose is an ancient, although still current, instrument of geographical location, in which the border axes of the four cardinal points are born at its center. It is an image in which letters are seen as verbal signs. They minimize words, directions, flows... This visual hybrid is one of the aesthetic and metaphorical marks of the work of José Leonilson Bezerra Dias, a Brazilian artist who, in 33 years of life, has built a repertoire of four thousand artistic products and many verbal-image unknowns. His work is usually linked to the context of homosexuality in the 1980s in Brazil, especially marked by the outbreak of the HIV virus, from which Leonilson would succumb. However, his canvases of ink, sewing or his sculptures go further: they are loose pages of a painful and desiring writing of the self, sometimes assumed as true, sometimes as falsified. In this intersection of truths, various forms of art are a modality of creation and self-registration, which takes place in their agendas, in their works and even in the verses of the canvases. In 2017, Leonilson's most intimate desire – perhaps as strong as the desire to be loved in a reciprocal way – is conquered: to write a book. Its raisonné catalog is published, bringing the compilation of all its production. On the pages, a wealth of material by and for researchers whose work has served as a reference from renowned artists in the visual arts to body tattooers, such as Leonilson's, flammable. This collection, however, still raises questions. His diaries are not fully available, his canvases and interventions are constantly being appreciated in new exhibitions or contemporary performances. From the social network “Instagram” we gathered part of this expansion around a virtual page whose title names this thesis. Thus, with the instigation of concepts such as post-autonomous literature (LUDMER, 2007); Expanded literature (PATO, 2012) and nonspecificity in contemporary aesthetics (GARRAMUÑO, 2014) proposes a doctoral study on the expansive character in the works of Leonilson, or Leó to the most intimate and on the contemporary reverberations of the artist's production. His lyrical word and his subjective narrative combine with paints, embroidery and other materials in the construction of a poetic place bordering between languages, showing a fragmented subject in a time of democratic opening and viral castrations. The compass rose, sign of Leo and of this research in comparative literature, indicates multiple paths. Their routes are constructed from questions in the form of affections: What is Leonilson's word-image made of? Are there limits to its expansion? What does the growing popularization of an artist keep from interdicts and questions?